Textbooks and the teaching of history in the Spanish Philippines: business, censorship and social control - Inarejos, Juan Antonio (Historia y Memoria de la Educación, 2018)
The content and focus of the history subjects contemplated in the reform of the Primary Instruction of the Philippines of 1863 were conceived by the colonial authorities as an effective mechanism of social control. That is why textbooks destined for primary and secondary education were subject to the tight control and censorship of the religious authorities in charge of colonial education. But this educational reform also opened enormous horizons of economic enrichment through the business of selling textbooks intended for Philippine educational institutions in the framework of the conservative liberal historiographical tradition. Finally, during the final years of the century, when the protests against peninsular domination in the archipelago increased, the colonial authorities supported the distribution in the form of school manuals of a series of markedly patriotic works that extolled the colonizing work of the metropolis.